Use of bacteriophages to control antibiotic-resistant aeromonas salmonicida populations - Carl F. Uhland; Serge Parent; Sandra Imbeault; Jean-François Blais; Michel Lagacé (Revue des sciences de l'eau, 2007)
Aquaculture represents an increasingly important source of food fish worldwide. The aquaculture industry currently produces between 25 and 30% of all seafood for human consumption. In Canada, salmonids (salmon, rainbow trout, arctic char and brook trout) account for the majority of food fish production. Furonculosis involving the bacterium Aeromonas salmonicida is one of the most important infections observed in salmonid farms. An A. salmonicida infection results either in morbidity and mortality with few clinical signs, or in weakened fish with skin ulcers that make them unmarketable for human consumption. The A. salmonicida bacterium uses a number of mechanisms to counteract the natural barrier of the immune system. Bacterial growth is encouraged by an increase in the ambient temperature and in the concentration of organic matter in the water.During recent years, a relationship between therapeutic failures and the development of bacterial resistance to antibiotics has been reported in salmonid farms. This problem is complicated by the fact that only four antibiotics are authorized for the aquaculture industry in Canada. One consequence of this increasing resistance is a renewed interest in alternative therapies and prevention. Bacteriophages (bacterial viruses) may represent one such alternative. In recent decades, interest in bacteriophages as antibacterial agents has been growing in the Americas and in Asia. Some researchers have tried to exploit the potential of bacteriophages to reduce bacterial populations in infections affecting humans, while others have tried to identify uses in veterinary medicine.The overall objective of this research was to explore a new treatment against furonculosis infection based on the use of bacteriophages to inhibit growth of A. salmonicida cells. In this study, we looked at 19 strains of A. salmonicida, resistant to zero, one, two or three antibiotics, and evaluated their sensitivity to 12 bacteriophages. The results showed that the antibiotic-resistant strains were sensitive ...